Educação e diversidade : um olhar para a formação continuada de professores da rede municipal de Goiânia - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The main objective of this study was to “analyze the implementation of public policies for diversity in the continuing education of teachers of the Center for the Training of Education Professionals (CEFPE), which has the diversity and continuous training of teachers in the city of Goiânia”. An integral part of the organizational structure of the Municipal Department of Education and Sports (SME). As specific objectives, we focus research on the following topics: identify the work proposal for CEFPE diversity; to know the formative actions offered by CEFPE and to verify if they comply with the guidelines contained in the public educational policies and if they contribute to the continued formation of teachers for and in the wide diversity; to analyze the perception of the subjects involved in the research in relation to the continuing education courses for CEFPE diversity. Diversity in school and as a training theme for teachers has been the focus of academic and non-academic discussions. Consequently, this fact has provoked changes of vision of public leaders, schools and teachers. The relevance of this study is anchored in the urgent need to know the initiatives aimed at teacher training for diversity in the municipality of Goiânia. With the vision and the "look at the diversity" of those involved in education in the city of Goiânia, we perceive that the process of discussing diversity as a theme of continuing education is in the process of maturation, although it presents some shortcomings generated by the lack of a clear policy and the difficulty of discussing some themes related to diversity, for example, issues of gender and religion. However, it is clear that both managers and teachers recognize the need to work on the theme and importance for pedagogical practice and the recognition of the other, especially the recognition of individual potentialities.
Keywords: Formação de professores; Diversidade; Políticas públicas educacionais; Teacher training; Diversity; Public educational policies; CIENCIAS HUMANAS::EDUCACAO